2007
DOI: 10.1007/s00401-007-0327-1
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal motoneuron migration, differentiation, and axon outgrowth in spinal muscular atrophy

Abstract: Abnormal motoneuron migration, differentiation, and axon outgrowth in spinal muscular atrophy. Acta Neuropathologica, 115 (3). pp. 313-326. The role of heterotopic (migratory) motoneurons (HMN) in the pathogenesis of spinal muscular atrophy (SMA) is still controversial. We examined the occurrence and amount of HMN in spinal cord tissue from eight children with SMA (six with SMA-I and two with SMAII). All affected subjects were carrying a homozygous deletion of exon 7 in the SMN1 gene. Unlike controls, virtuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 51 publications
4
30
0
1
Order By: Relevance
“…In this respect, intramuscular administration of adenoviral vectors expressing cardiotrophin-1 improved motor performance and increased survival in a SMA model [59], indicating that cytokines might modulate the neurodegenerative process in SMA. The present data are in agreement with the report of gliosis in the spinal cord of SMAI and SMAII patients [47], and support the idea that also neuroinflammation should be considered as a potential therapeutic target for tackling SMA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this respect, intramuscular administration of adenoviral vectors expressing cardiotrophin-1 improved motor performance and increased survival in a SMA model [59], indicating that cytokines might modulate the neurodegenerative process in SMA. The present data are in agreement with the report of gliosis in the spinal cord of SMAI and SMAII patients [47], and support the idea that also neuroinflammation should be considered as a potential therapeutic target for tackling SMA.…”
Section: Discussionsupporting
confidence: 93%
“…Apoptotic mechanisms can also play a major role in motor neuron death in SMA, as suggested by data from human post-mortem specimens of SMA type I patients [43,44] and animal models [45,46]. Finally, it should be remembered that failure in motor neuron migration was proposed as the key step to understand motor neuron loss and hence pathogenesis in human SMA [47]. …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, we need to compare observations in human patients with the findings in model organisms. For example, in a recent study, SMA-I and SMA-II spinal cords showed a significant number of motor neurons that had migrated aberrantly toward the ventral spinal roots (Simic 2008; Simic et al 2008). These heterotopic motor neurons (HMN) were located mostly in the ventral white matter and had no axon or dendrites.…”
Section: Animal Models Of Smamentioning
confidence: 99%
“…In SMA, a significant number of motor neurons in the spinal cord die by a process characteristic of apoptosis (Simic et al, 2000;Tsai et al, 2006;Simic et al, 2008).…”
Section: Discussionmentioning
confidence: 99%